Essential Dutch grammar - Stern, Henry R. (New York : Dover, 1984)
Based on the premise that systematic study of grammar is a shortcut to language learning, ESSENTIAL DUTCH GRAMMAR helps the language student acquire fluency by emphasizing the similarities between English and Dutch and by concentrating on essentials, such as spelling, word order, parts of speech, and other elements of grammar--all illustrated with easy-to-understand examples.
Περιέχει ευρετήριο.
Keywords: Dutch language -- Textbooks for foreign speakers -- English; Ολλανδική γλώσσα -- Γραμματική; Dutch language -- Grammar; Autoformation; Dutch language -- Grammar; Dutch language; Enseignement des langues; Formation; Grammaire; Dutch language -- Grammar; Textbooks -- for English speakers; Textbooks; Textbooks